2015
DOI: 10.1007/s00775-015-1274-2
|View full text |Cite
|
Sign up to set email alerts
|

4-(2′-Pyridyl)imidazole as an artificial nucleobase in highly stabilizing Ag(I)-mediated base pairs

Abstract: A new artificial nucleoside 2 comprising 4-(2'-pyridyl)imidazole as the nucleobase was devised and incorporated into a series of DNA oligonucleotide duplexes. The propensity of 2 to form metal-mediated homo and hetero base pairs was investigated in various 13mer and 26mer duplexes. The artificial nucleoside readily forms Ag(I)-mediated homo base pairs of the type 2-Ag(I)-2, in which the Ag(I) ion resides in a [2 + 2] coordination environment. In addition, the combination with the previously established imidazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Similarly to 6PP–Ag(I)–6PP, the Ag(I) ion may bind via N1 or via N7. In both cases, a [2+1] coordination environment is proposed for the metal ion, in analogy to what has been found in other Ag(I)-mediated base pairs [ 26 , 33 ]. Weak additional binding via one of the carbonyl oxygen atoms cannot be ruled out though.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Similarly to 6PP–Ag(I)–6PP, the Ag(I) ion may bind via N1 or via N7. In both cases, a [2+1] coordination environment is proposed for the metal ion, in analogy to what has been found in other Ag(I)-mediated base pairs [ 26 , 33 ]. Weak additional binding via one of the carbonyl oxygen atoms cannot be ruled out though.…”
Section: Resultssupporting
confidence: 53%
“…As the formation of coordinate bonds between the artificial nucleobases and the metal ion typically leads to an increased stability of the duplex [ 2 ], monitoring the T m often represents a good indication for the formation of a metal-mediated base pair. Exceptions from this rule are rare, but are sometimes found in the case of non-planar metal-mediated base pairs [ 24 , 25 ] or when the metal-free duplex is exceptionally stable [ 26 ]. Figure 1 shows the melting curves of the duplex comprising a 6PP:6PP base pair in the absence and presence of one equivalent of AgNO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…At first, this discrepancy appears surprising, considering that fact that the base pairs should only differ in the relative orientation of their glycosidic bonds (cisoid vs. transoid). However, this may very well be due to the different length of the oligonucleotides under investigation, as previous publications had indicated that the thermal stabilization induced by metal-mediated base pair formation typically is larger for shorter oligonucleotides [59], as is the case here.…”
Section: Hetero Base Pairmentioning
confidence: 61%
“…It is a well-known phenomenon that metal-mediated base pair formation exerts a larger stabilizing effect if the stability of the metal-free state is reduced. 38 In summary, the study of duplexes II−IV shows that the most reliable light-triggered formation of an H− Cu(II)−H base pair is achieved when both hydroxypyridone residues initially carry an NPP protecting group.…”
Section: ■ Results and Discussionmentioning
confidence: 98%